Ethnomedicinal survey and mutagenic studies of plants used in Accra metropolis, Ghana. (10th February 2020) - Oppong Bekoe, Emelia; Agyare, Christian; Boakye, Yaw Duah; Baiden, Benedict Mbeah; Asase, Alex; Sarkodie, Joseph; Nettey, Henry; Adu, Francis; Otu, Priscilla Boatema; Agyarkwa, Benjamin; Amoateng, Patrick; Asiedu-Gyekye, Isaac; et al.
Abstract: Ethnopharmacological relevance: Majority of people living in Ghana and many other developing countries rely on traditional medicinal plants for their primary healthcare. These plants are used either alone or in combination to manage a wide range of ailments. However, most of these plants have not been investigated for their mutagenic effects. Aim of the study: This study, therefore aimed at evaluating the mutagenic activity of the most frequently used medicinal plants amongst Ghanaians living within the Accra metropolis, Ghana. Materials and methods: Validated questionnaires were administered to 53 herbalists and herbal medicines dealers in the Makola, Madina and Nima communities. Plants that were identified as being frequently used were investigated for their mutagenicity using the Ames test. Results: A total of 110 medicinal plants belonging to 53 families were identified as most frequently used plants in the study sites. These are used to treat various ailments including gastric ulcer, fever, malaria, male impotence, diabetes, typhoid, high blood pressure and candidiasis. Thirteen samples (52%) showed moderate to high mutagenicity in the TA 100 bacterial strain before and after metabolism with rat liver enzyme. Conclusions: The study showed that over half of the frequently used medicinal plants showed moderate to high mutagenicity before and after metabolism at the concentration of a 100 μg/mL. This may have implications for the safety of those who use them to manage diseases. These findings will suggest the need for an in-depth study of the mutagenic potentials of plants commonly used by indigenous people and more especially for those exhibiting high mutagenicity in this study. Graphical abstract: Image 1